The lessons of terror : a history of warfare against civilians : why it has always failed and why it will fail again - Carr, Caleb, 1955-2024. (New York : Random House, 2002)
We think of terrorism as a relatively modern phenomenon used by fringe political and religious groups, but The Lessons of Terror demonstrates that it is a practice that has existed since time immemorial, and has been employed by national armies as well as extremists. Carr's exploration of two thousand years of terrorism reveals the tactic's consistently self-defeating nature: Far from prompting submission, it only stiffens enemy resolve, and never leads to long-term success or peace. Carr provides a critical historical context for understanding not only individual terrorist acts today, but the Middle East conflict as well.
A catastrophe, not a cure -- Dulce bellum inexpertis -- Industry and cunning -- Covenants without the sword -- Honor has no effect on them -- To preach hatred -- Violence to its utmost bounds -- Fascinated by terror -- This fundamentally repugnant philosophy -- Shake hands with murder -- Profit or preservation?
Includes bibliographical references (pages 257-259) and index.
Keywords: Terrorism; Terrorism -- History